2017
DOI: 10.1016/j.cognition.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy violations promote learning in young children

Abstract: Children, including infants, have expectations about the world around them, and produce reliable responses when these expectations are violated. However, little is known about how such expectancy violations affect subsequent cognition. Here we tested the hypothesis that violations of expectation enhance children’s learning. In four experiments we compared 3- to 6-year-old children’s ability to learn novel words in situations that defied versus accorded with their core knowledge of object behavior. In Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
71
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 98 publications
7
71
2
Order By: Relevance
“…Our findings appear to be inconsistent with recent research demonstrating that violations of expectations support novel learning in infants and children [27, 28] and with proposals suggesting that violations of expectations play an important role in acquiring novel regularities [11, 2933]. One possibility for this inconsistency is that predictability and violations of predictions may have different effects on learning because they elicit different responses.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings appear to be inconsistent with recent research demonstrating that violations of expectations support novel learning in infants and children [27, 28] and with proposals suggesting that violations of expectations play an important role in acquiring novel regularities [11, 2933]. One possibility for this inconsistency is that predictability and violations of predictions may have different effects on learning because they elicit different responses.…”
Section: Discussioncontrasting
confidence: 99%
“…If novel information is presented shortly after a predictable event, as in the current study, learning may benefit because the predictable events cause an immediate response that heightens attention [8]. The benefits of learning from violations of expectations may not be seen until later, when the system has taken time to interpret the event as a prediction error, signaling the need to further explore the unexpected situation [8, 27, 28]. Another important factor to consider is the manner in which predictability is manipulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that young children are sensitive to when evidence presents a stark conflict with their expectations, and selectively explore to resolve those inconsistencies (Legare, 2012;Legare, Wellman, & Gelman, 2010;Stahl & Feigenson, 2015, 2017. The current research focuses on whether, in cases where a conflict may be easily overlooked or dismissed, pedagogical demonstration of conflicting evidence may facilitate children's ability to use it to revise their beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we note that previous research has largely overlooked the issue of what leads children to recognize that a conflict is relevant to their ongoing process of hypothesis formation and revision, and that they ought to Pedagogy and counterevidence 8 search for additional evidence that might help them resolve that conflict. In prior work, the conflicts have been quite stark, either because the evidence conflicted with children's intuitive conceptions of the physical world (Bonawitz et al, 2012;Stahl & Feigenson, 2015, 2017, or because the initial rule was explicitly taught and conflict was made vivid through deliberate demonstration or prompts for explanation (Legare, 2012;Legare et al, 2010).But in many cases, evidence may not present such a stark conflict. Clearly evidence that conflicts with the laws of the natural world is rare.…”
mentioning
confidence: 95%